A novel fiber-grafting-sensing testing method for temperature deformation of piezoelectric composites. (January 2020) - Bai, Zhiqi; Wang, Likun; Zhang, Xingcai; Ran, Chen; Liao, Qingwei; Qin, Lei
Abstract: The deformation of piezoelectric composite has many deadly effects on the transducers and the sonar systems, but the relative testing method never been focused. Here we developed a novel fiber-grating-sensing method for the study of temperature deformation of the piezoelectric composites for the first time. With the increase of temperature, the deformations of the piezoelectric composite in three dimensions increased, and the increasing speeds (all speeds means slop of fitted line) were 1.4 × 10 −3 (length), 1.8833 × 10 −4 (width) and 3.1439 × 10 −5 (thickness), respectively. After adding the deform information the data for the frequency constant and dielectric constant were revised. The decreasing speed of frequency constant lowered from −2.0373 to −2.0263. The increasing speed of dielectric constant lowered from 2.6779 to 2.6580 in the range of 25 °C–75 °C, and from 1.9647 to 1.9559 in the range of 75 °C–125 °C. Highlights: It is one first work on 3D distributed network test method. Precise and consistent test at any direction. Test with one single fiber. Only one channel needed.